Real-World Experience with Topical 5-Fluorouracil 4% (40 mg/g) Cream for the Treatment of Actinic Keratosis - Giulia Briatico; Gabriella Brancaccio; Camila Scharf; Eugenia Veronica Di Brizzi; Sebastiano Pellerone; Stefano Caccavale; Caterina Mariarosaria Giorgio; Enrico Maria Procaccini; Elvira Moscarella; Giuseppe Argenziano (Mattioli1885, 2023)
Introduction:5-fluorouracil (5-FU) is one of the most effective topical treatments for actinic keratosis (AK). A new 4% formulation of 5-FU was recently approved in Europe. Objectives:This study aimed at evaluating 4% 5-FU cream safety and effectiveness in a real-world setting. Methods:Adult AK patients were retrospectively selected from the University of Campania Dermatology Unit database. Selection criteria included a diagnosis of non-hyperkeratotic, non-hypertrophic AK (Olsen grade I and II) of the face, ears, and/or scalp, treatment with 4% 5-FU once daily for 4 weeks, and at least 3 follow-up visits (4 and 8 weeks after treatment initiation, and 6 months after treatment end). The primary objectives were to evaluate AK lesions improvement at 8 weeks and relapse rate at 6 months. Patient-reported erythema and burning sensation intensity were also assessed at 4 weeks. Results: Ninety-eight patients were included in this analysis (male/female 80/18, mean age 74.7 years). AK lesions improvement at 8 weeks resulted complete or significant in 74.5% and 20.4% of the patients, respectively. At 6 months, 65.3% of the patients did not show AK relapses. Burning sensation at 4 weeks was reported as light, moderate, or absent by 44.9%, 22.4%, and 31.6% of the patients, respectively. Erythema was reported as light, moderate, or absent by 37.8%, 51%, and 10% of the patients, respectively. Burning sensation and erythema disappeared gradually during follow-up. No other side effects were reported. Conclusions:In this real-world study 4% 5-FU proved to be highly effective for AK lesions clearance with a favorable safety profile.